Produção de filmes supercondutores de nióbio e de sistemas híbridos crescidos por Magnetron Sputtering DC - Carmo, Danusa do (2012)
Currently, several research groups have been devoted to the production of superconducting films. This interest lies on the facility of their manipulation, on the understanding of basic concepts of the superconductivity and, especially, in the possibility of reducing them to dimensions compatible to their application as devices. Therefore, there is a great technological and academic interest in this issue. The most used material in superconducting devices is the niobium (Nb) and its alloys. Although Nb has been known as superconductor since 1930, the interest in excellent films of this material still remains. In this work, using a DC magnetron sputtering technique, we have developed an experimental method that allows one to produce superconducting Nb films of good quality - transition temperature of 9.1 K and transition width of 0.2 K. Therefore, we performed a systematic study of the setup parameters that influences the structural and superconducting properties of the films. In particular, we have analyzed the evolution of the lattice parameter, average grain size crystalline and critical temperature. Such values have been compared in a diagram. Nb films exhibit flux avalanches at certain values of field and temperature. We have detected and visualized the occurrence of avalanches of magnetic flux in Nb films and, in order to suppress the abrupt flux penetration, we have coupled to the films of thickness of 200 nm, thick metal layers of aluminum, silver and copper of different thicknesses, so called hybrid systems - Superconductor/Normal Metal. In this work piece, two experimental techniques have been employed: magnetometry and magneto-optical imaging. A partial suppression of avalanches in the hybrid systems has been observed.